English Foreign Language Learners Kinesics on Teaching Performance - Hajjah Zulianti (IAI Ma'arif NUMetro Lampung, 2017)
This research entitle English foreign language learners kinesics on teaching performance aims to mention and to describe the forms and the function of kinesics used by EFL learners on teaching performance, and to describe the importance of kinesics in teaching activity. This research is descriptive qualitative research. The data of the research are taken from EFL learners' teaching performance on sixth semester at STKIP PGRI Bandar Lampung. The researcher observes the learners' kinesics in teaching activity by using observing method and noting technique. In analyzing the data, the researcher uses description method. The result shows that there are twenty kinds of kinesics acted by the trainee, those are sitting in relaxing, arms crossed in front of the chest, standing in relaxing, walking around the class, checking the time, stroking the chin or beard, smile, happily surprised, wrinkle forehead, nodding head, shaking head, thumbs up, pointing finger, counting hand, waving hand, looking up, eye following, squinting, look in eye and breaking or making eye contact. Keywords: Kinesics, EFL Learners, Teaching Performance